Flammability action of tires material after adding flame inhibitor - Baghdad Science Journal (مجلة بغداد للعلوم)
Magnesium hydroxide was used as flame inhibitor to increased flame resistance for tires .Magnesium hydroxide was adding with (5%,10%) weight percents to rubber master batch of tire and then exposed the resulting material to a flame generated from gas torch with (10 mm) exposure distance . Method of measuring the surface temperature opposite to the flame was used to determine the heat transferred through tire material. The results were obtained shows enhanced flame resistance for tire by added magnesium hydroxide and this resistance increased by increasing hydroxide Percentage .